The Interactions Between Sediments and Water 1997
DOI: 10.1007/978-94-011-5552-6_5
|View full text |Cite
|
Sign up to set email alerts
|

The Freshwater Floc: A Functional Relationship of Water and Organic and Inorganic Floc Constituents Affecting Suspended Sediment Properties

Abstract: Abstract. Flocculated fine-grained sediment is a complex matrix of microbial cmnmunities and organic (detritus, cellular debris and extracellular polymers) and inorganic material. Suspended floes within any aquatic system play a significant ecological role as they can regulate the overall water quality through their physical, chemical and/or bioloocal activity. This paper investigates the complex structural matrix of nverine floes over a large range of magnifications using correlative microscopic techniques. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
3
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(145 citation statements)
references
References 22 publications
4
135
3
3
Order By: Relevance
“…In contrast, Figure 3f shows a composite form with a much looser overall structure (and a smaller range of constituent grain sizes) with large voids that may be indicative of formation solely by flocculation within the proglacial stream. In the absence of organic binding agents [see Droppo et al (1997)], the composite particles shown in Figure 3a, c and f, the upper part of figure 3b, and the outer section of figure 3e, may result solely from electrochemical flocculation processes. To the authors' knowledge, this mechanism of floc formation has not been reported previously in the freshwater fluvial environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Figure 3f shows a composite form with a much looser overall structure (and a smaller range of constituent grain sizes) with large voids that may be indicative of formation solely by flocculation within the proglacial stream. In the absence of organic binding agents [see Droppo et al (1997)], the composite particles shown in Figure 3a, c and f, the upper part of figure 3b, and the outer section of figure 3e, may result solely from electrochemical flocculation processes. To the authors' knowledge, this mechanism of floc formation has not been reported previously in the freshwater fluvial environment.…”
Section: Resultsmentioning
confidence: 99%
“…Continuous in situ measurement of such events using a field-portable laser backscatter probe, such as that described by Phillips and Walling (1995), would allow such controls to be explored further. In addition, monitoring the downstream passage of a glacially sourced suspended sediment pulse may provide further insights into freshwater flocculation processes (including electrochemical mechanisms), since both the proportion of organic matter and bacterial activity are likely to increase downstream; see Petticrew, (1996) and Droppo et al (1997). Equally, information on the mineralogy, structure and abundance of source-derived aggregated suspended particles may provide insights into the nature of the sub-glacial drainage system and sediment sources; see Eyles (1978), Collins (1979Collins ( , 1989, and Foster et al (2000).…”
Section: Discussion and Research Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…In its simplest form, the term can refer to the primary mineral particles (e.g., sand, silt, clay), however, much of the soil is moved as aggregates which are a cohesive agglomeration of both inorganic and organic matter, which may have different physical and biogechemical characteristics in comparison to the primary particles of which they comprise (Buffle and Leppard 1995a;Buffle and Leppard 1995b;Droppo et al 1997;Droppo 2001). Therefore, making conclusions about the mobilization and transport of sediment based on absolute (i.e., physically and/or chemically dispersed) particle size distribution may result in errors as soil moves as aggregates and, therefore, the effective or aggregate particle size distribution may be more informative .…”
Section: Particle Selectivitymentioning
confidence: 99%
“…Flocculation refers to aggregation of living and non-living biological material and mineral particles that can occur within the water column (Droppo et al 1997). …”
Section: Sediment Dynamicsmentioning
confidence: 99%